MORAL MESSAGE OF L.A. LIGHTS ADVERTISEMENT “JANGAN MAU DIADU, JANGAN MAU DIPECAH” - Assiddiki, Rifki; Faristiana, Andhita Risko (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
ABSTRACT: The purpose of this research is to determine the moral message and to find out the meaning of denotation, connotation, and to find out the myth of L.A. Cigarette advertising. The data collection technique used a semiotic analysis research method from Roland Barthes. The results of the analysis of the data found indicate that the moral message contained in this study reflects the life of a person, both from the lower middle class or the upper middle class, must be able to face problems and not leave problems and not leave problems but solve problems so that they will be resolved soon. The meaning of denotations, connotations, and myths in this study is that each individual must have an attitude of solidarity, responsibility, reciprocal forgiveness, be oneself, regret actions when making mistakes, dare to take risks, and be confident.Keywords: Moral Message, Advertising, LA Lights